Variability of activity profile during medium-sided games in professional soccer - Rago, V.; Silva, J. R.; Mohr, M.; Barreira, D.; Krustrup, P.; Rebelo, A. N. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: In Southern European countries it is very frequent to perform medium-sized games (MSG) as last training drill. We analyzed the individual variability and changes in activity patterns during MSG throughout the preseason. METHODS: Activity profile during MSGs (10v10+goalkeepers, duration: 10-min, field length: 50 m, width: 90 m, area per player: 204.5 m2) was quantified using a GPS in 14 professional male players (6 defenders, 5 midfielders 5 and attackers). RESULTS: Inter-individual variability was higher for high-intensity (HIR), very-high speed (VHS), maximum acceleration (Accmax) and maximum deceleration (Decmax) distance (CV=25.2 to 43.3%), compared to total distance (TD), total acceleration (Acctot) and total deceleration (Dectot) distance (CV= 8.3 to 18.3%). Defenders showed higher variability in TD, HIR, VHS, Acctot and Dectot (ES= 1.30 to 11.28) compared to the other field positions, whereas attackers showed higher variability in HIR, VHS Accmax and Decmax (ES=-4.92 to 2.07) than other the field positions. Variability in TD regularly increased (ES= -2.13 to -0.91) towards the end of the preseason, while HIR and VHS variability tended to increase over the 3rd and the 4th preseason week (ES=-0.94 to -3.05). However, the behavior of variability across the preseason period was more unpredictable for Acctot and Dectot, both decreasing in the 3rd week (ES= 0.70 to 1.20), while Decmax increased in the 4th week (ES=-0.91±0.59). CONCLUSIONS: During MSGs, individual variability of activity differs among field positions, and tends to increase with either speed or acceleration intensity, underlining the need of an individualized approach for training load monitoring.